Early Intervention in Post-operative Infectious Spondylodiscitis: Outcome of Aggressive Transforaminal Lumbar Interbody Fusion - Krishnan A; Dave BR; Degulmadi D; Mayi S; Rai R; Bang P; Dave M; Chauhan V; Bali S; Charde P; Anil A; Krishnan P (Malaysian Orthopaedic Journal)
Introduction: Conservative and surgical approach timeline in post-operative spondylodiscitis (POS) following lumbar disc herniation (LDH) surgery is ill defined, and patients have a protracted recovery phase with social, psychological, and financial implications.